The Impact of Corporate Governance on The Effectiveness of Internal Audit Exploratory Study - Aldurrah Waleed Khalid (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In order to achieve the objectives of the research and arrive at the best methods and methods for detecting the impact of corporate governance and knowing the extent of its impact on the effectiveness of internal audit as a treatment for the research problem, the researcher will adopt the descriptive analytical approach and this approach is applied in many research and studies, especially those that deal with social and administrative phenomena related to daily practices and The data that is collected, analyzed, discussed and presented in a scientific and interconnected manner in a manner that serves the objectives of the research.